Experimental aspects of reproductive physiology at altitude - San Martín, Mauricio (1945)
In this paper, we present the results of five years of experimentation on playing at altitude. Since 1940, when the lethal action of dilutor of tartrates on spermatozoa demonstrated to date, we have advanced in the study of reproduction, but since this topic so broad and so much interest for its practical implementation, we believe our results should be considered as a preliminary survey in this study. Each point must be reviewed and analyzed carefully, because of the results obtained in experimental work depends establishing scientific guidelines for the reproduction and development of animal population of our mountain.